2023
DOI: 10.1002/jev2.12298
|View full text |Cite
|
Sign up to set email alerts
|

Special considerations for studies of extracellular vesicles from parasitic helminths: A community‐led roadmap to increase rigour and reproducibility

Abstract: Over the last decade, research interest in defining how extracellular vesicles (EVs) shape cross‐species communication has grown rapidly. Parasitic helminths, worm species found in the phyla Nematoda and Platyhelminthes, are well‐recognised manipulators of host immune function and physiology. Emerging evidence supports a role for helminth‐derived EVs in these processes and highlights EVs as an important participant in cross‐phylum communication. While the mammalian EV field is guided by a community‐agreed fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 86 publications
0
21
0
Order By: Relevance
“…To verify their presence and characterize the EVs (size and morphology), both NTA and TEM were used (EVtrack ID EV220006), as recommended by White et al. ( 2023 ). The isolated EVs were visualized by TEM, confirming the presence of typical round‐shaped vesicles within the size range of 30–200 nm (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify their presence and characterize the EVs (size and morphology), both NTA and TEM were used (EVtrack ID EV220006), as recommended by White et al. ( 2023 ). The isolated EVs were visualized by TEM, confirming the presence of typical round‐shaped vesicles within the size range of 30–200 nm (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The isolation of EVs from parasites was performed as described previously (Sánchez‐López et al., 2020 ) and following the recent recommendations issued by White et al. ( 2023 ). Briefly, ESP were centrifuged at 16,000 × g/20 min at 4°C and filtered through 0.22 μm membrane filters to exclude large EVs.…”
Section: Methodsmentioning
confidence: 99%
“…specific epitopes. The EV fractions of the mentioned extravesicular ESP and intravesicular fluid fractions were isolated and purified with a protocol from Eichenberger et al ( Eichenberger, 2021 ), according to MISEV guidelines ( Théry et al., 2018 ; White et al., 2023 ). In brief, a combination of differential ultracentrifugation followed by Opti-prep ® discontinuous gradient (ODG) was used to purify EV fractions (fractions 3 to 8).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, substantial research was focused on the description of extracellular vesicles (EVs) in multiple helminth species. Helminths release EVs into their environment, which have various effects that are relevant in parasite-host interactions ( White et al., 2023 ). So far, this work was mainly focused on the characterization of EV-molecules and their specific interactions with host cells and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, studies focused to investigate molecules shaping the adaptation of these parasites to their natural hosts are rather limited ( Mehrdana and Buchmann, 2017 ; Palomba et al., 2020 ; Trumbić et al., 2021 ; Harbar et al., 2022 ). Recent studies have revealed that extracellular vesicles (EVs) represent a new paradigm in the “cross-talk” between parasites and their hosts, playing a crucial role in pathogenesis’s mechanisms including the parasite’s capacity for immune evasion ( Marcilla et al., 2012 ; Barteneva et al., 2013 ; Marcilla et al., 2014 ; Coakley et al., 2015 ; Sánchez-López et al., 2021 ; White et al, 2022a) . In addition, helminth-derived EVs are recently proposed as key players in helminth-microbiota crosstalk ( Rooney et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%